Boosting Confidence: Kampung Inggris Students’ Journey in Improving Speaking Skill - Dwi Astuti; Mustofa, Mutmainnah; Dzulfikri, Dzulfikri; Subarjo, Subarjo (Universitas Muhammadiyah Yogyakarta, 2026)
Background: Speaking confidence is a critical affective factor in English as a Foreign Language (EFL) learning, yet it remains one of the most challenging aspects for learners, particularly in non-native contexts like Indonesia. This study offers a novel perspective by exploring the emotional and experiential dimensions of speaking confidence through the lens of students enrolled in Kampung Inggris, a non-formal, immersive English learning environment. Objective: This research investigated how EFL learners develop speaking confidence, overcome anxiety, and engage in authentic communication through daily interaction. Methods: Using a qualitative narrative approach, the study was conducted in Kampung Inggris, Pare, East Java, with three EFL learners from varied educational backgrounds and varying lengths of stay. Data were collected through semi-structured interviews, reflective journals, and observational notes, and they were analyzed thematically to identify patterns in emotional readiness, peer support, and strategic adaptation. Findings: Consistent exposure to English, emotionally supportive peer interaction, and empathetic tutor feedback significantly contribute to EFL learners' transformation from hesitant speakers to confident communicators. Informal practice and community-driven support emerged as key elements in fostering fluency and self-assurance. Conclusion: Immersive and emotionally supportive communication environments play a vital role in shaping EFL learners’ speaking confidence, and they should be considered in the design of learner-centered language programs.